## The average age of A and B is 30 years that of B and C is 32 years and the average age of C and A is 34 years. the age of C is?

- 33 years
- 34 years
- 35 years
- 36 years

As Average age of a and b is 30 years

=> ( a + b ) / 2 = 30

**=> a + b = 60 –eq(1)**

As Average age of b and c is 32 years

=> ( b + c )/ 2 = 32

**=> b + c = 64 –eq(2)**

As Average age of c and a is 34 years

=> (c + a) /2 = 34

**=> c + a = 68 –eq(3)**

by equaction 2

b + c= 64

**=> b = 64 -c**

using –1

a+ (64 – c ) = 60

**=> a = c – 4**

using 3

(c – 4) + c = 68

**=> c = 72/2 = 36**

Hence age of c= 36 years.